2016
DOI: 10.1016/j.dsr2.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute ocean acidification on spatially-diverse polar pelagic foodwebs: Insights from on-deck microcosms

Abstract: The polar oceans are experiencing some of the largest levels of ocean acidification (OA) resulting from the uptake of anthropogenic carbon dioxide (CO 2 ). Our understanding of the impacts this is having on polar marine communities is mainly derived from studies of single species in laboratory conditions, while the consequences for food web interactions remain largely unknown. This study carried out experimental manipulations of natural pelagic communities at different high latitude sites in both the northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 81 publications
0
4
0
1
Order By: Relevance
“…The first cruise (D366) took place in northwest European shelf seas during summer on the RRS Discovery (2011 June 6-July 12) (Richier et al, 2014). Two subsequent cruises (JR271 and JR274 respectively) were carried out in the Arctic (2012 June 1-July 2) (Poulton et al, 2016) and Southern (2013 January 9-February 12) (Tarling et al, 2016) oceans, both on board the RRS James Clark Ross. Locations, oceanographic settings, and treatments applied within each experiment are presented in Tables 1 and 2. Specific cleaning and handling techniques were followed during setup of each of the experiments.…”
Section: Seawater Collection and Experimental Set Upmentioning
confidence: 99%
“…The first cruise (D366) took place in northwest European shelf seas during summer on the RRS Discovery (2011 June 6-July 12) (Richier et al, 2014). Two subsequent cruises (JR271 and JR274 respectively) were carried out in the Arctic (2012 June 1-July 2) (Poulton et al, 2016) and Southern (2013 January 9-February 12) (Tarling et al, 2016) oceans, both on board the RRS James Clark Ross. Locations, oceanographic settings, and treatments applied within each experiment are presented in Tables 1 and 2. Specific cleaning and handling techniques were followed during setup of each of the experiments.…”
Section: Seawater Collection and Experimental Set Upmentioning
confidence: 99%
“…Other Antarctic pelagic species investigated include copepods (Bailey et al 2016), where acidification had little or no effect on development of early life stages, and krill where Kawaguchi et al (2011) found no effect on embryos and larvae of elevating CO 2 to 1000 µatm but found negative impacts at 2000 µatm. In a microcosm-based community-level study, Tarling et al (2016) showed that exposure to pCO 2 levels of 750 and 1000 µatm altered the community balance, and the interaction between copepods and their dinoflagellate prey was particularly affected. It should be noted that all of the pelagic experimental studies, because of restrictions to shipboard experiments, have been short-term, often with large changes to levels of pCO 2 in the system to values beyond those predicted for the year 2100, and as seen for benthic species, increasing the duration of exposure significantly alters the outcomes of experimental trials.…”
Section: Ocean Acidification In Antarcticamentioning
confidence: 99%
“…This plasticity is demonstrated by the high levels of variability in krill's association with and apparent dependence on sea ice (Meyer et al, 2017) and by rapid acclimation of individuals to the effects of reduced pH (Saba et al, 2021). Adults are able to survive long periods without food using a combination of lipid reserves and reductions in body size (Quetin et al, 1994;Tarling et al, 2016b). Krill have successfully colonized a range of habitats from the ocean surface to abyssal depths, and from continental ice shelves to the APF (Atkinson et al, 2008).…”
Section: Resiliencementioning
confidence: 99%
“…Effects from the gradual increase in OA are hard to determine experimentally, but in an acute response microcosm experiment, Tarling et al (2016b) found that copepods show a stronger preference for dinoflagellates when in elevated pCO 2 conditions, demonstrating that changes in food quality and altered grazing selectivity may be a major consequence of OA (Tarling et al, 2016b).…”
Section: Response To Driversmentioning
confidence: 99%